ROLE OF NATIONAL CULTURAL CENTERS IN PROVIDING INTERNATIONAL HARMONY - Gulyamova Aziza Nigmatovna (Scholar Express Journal, 2023)
This article is dedicated to the Republican Inter-National Cultural Center in the Republic of Uzbekistan, in which the importance of this center in the environment of inter-ethnic harmony and solidarity, friendship and solidarity is analyzed.
Keywords: nation; culture; center; custom